Makna Kepemimpinan Bupati Gresik dalam Perspektif Kepemimpinan Islami - Shobron Jamil; Rahmat Agus Santoso (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The purpose of this study is to find out the meaning of Siddiq, Amanah and Tabligh based on the perspective of the Regent of Gresik Regency, Mr. Fandi Akhmad Yani and to find out the relationship between Siddiq and Amanah towards Tabligh and Fathonah. This study uses a qualitative method with a phenomenological study approach. This research data collection technique through observation, interviews, and documentation. The results of this study are in the form of siddiq's meaning or essence based on the perspective of the Regent of Gresik Mr. Akhmad Yani, namely a leader who implements siddiq-characteristic Islamic leadership must have a trusted character in every program that is run and be transparent with all policies taken for prosperity the society he leads. The meaning or essence of Amanah is based on the perspective of the Regent of Gresik, Mr. Akhmad Yani, that is, a leader who applies Islamic leadership characterized by Amanah must have high integrity in carrying out the programs he has promised. In addition to high integrity, a leader must also be able to realize the programs promised to the community. The meaning or essence of Tabligh is based on the perspective of the Regent of Gresik, Mr. Akhmad Yani, namely a leader who implements Islamic leadership characterized by Tabligh must have a high level of concern and have an attitude of protecting the community he leads.